FEM Simulation of Polycarbonate Alloys-made Sheet under a Drop Weight Impact Test: Deformation and Failure Performances - M. Nizar Machmud; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2012)
This paper presents a study of deformation and failure performances of a plastic sheet made of polymer alloys subjected to drop weight impact of a cylindrical mass with hemispherical tip at a certain velocity by using dynamic explicit finite element code of MSC. Dytran. An available material model in the finite element system, called piecewise linear plasticity, was applied in the simulation for describing the large strain, non-linear behavior of the polymeric materials. Maximum plastic strain failure criterion was used to simulate the impact failure. In the simulation, the mass served as a rigid surface strikes perpendicularly the potential impact region of an arbitrary designed- plastic sheet that was considered in the form of a fully-clamped circular thin plate. Contact between the mass and plate was applied and friction coefficient m between the mass and plate was assumed to be a constant value of 0.3. In order to study effect of the assumed friction coefficient value, additional simulations of the impact test have been performed using m = 0. Some limitations in the use of the material model were illustrated through the analysis of results from two types of tough polycarbonate (PC) alloys: PC/ABS and PC/PBT blends. Impact force-displacement relationships of each alloy were then compared to the test result.